Comparison of Epithelium-off versus Epithelium-on Accelerated Corneal Cross-Linking in keratoconus patients - Ali, Ammar Bassam; Darwish, Taym Rafeek; Youssef, Habib Abdullatif (Journal of medical and pharmaceutical sciences, 2022)
Background: Keratoconus is a slowly progressive disorder characterized by a thinning and protruding cornea. Keratoconus leads to a significant disturbance of vision. Corneal sclerotherapy is a photochemical reaction between the photosensitive riboflavin (vitamin B2) and ultraviolet A (UV type A), which results in the formation of free oxygen radicals that increase the bonds between collagen fibers in the corneal parenchyma, which is done in order to increase the energy of the corneal sclerotherapy. Shortening the exposure time so that it becomes more convenient and comfortable for the patient, and corneal cross-linking has two modes: with epithelium removal and without removal. Oobjective: Comparison of the efficacy of accelerated corneal cross-linking with and without epithelium removal in patients with progressive keratoconus. Research materials and methods: In this prospective study, (27) eyes of (16) progressive Keratoconus patients underwent accelerated corneal collagen cross-Linking (ACXL), (12) Epithelium-off (Epi-off) and (15) Epithelium-on (Epi-on) randomly in the Ophthalmology Department in Tishreen University Hospital. Uncorrected visual acuity (UCVA) , best corrected visual acuity(BCVA) ,spherical equivalent (SE), maximum keratometry (K max) and corneal thinnest point(CTP) for all eyes were measured before and after 1, 3, 6 and 12 months of ACXL. Results: UCVA and BCVA improved significantly in Epi-off and Epi-on with non-significant changes between the two groups. There were no significant changes in the K max or spherical equivalent in either of the two groups or between them during our follow-up. There were no significant differences in the values of corneal thinnest point between the two groups or even in the Epi-on group, while we found a significant decrease in the Epi-off group after the first, then it increased during the 3, 6, and 12 months of the follow-up and reached the basic value. Conclusion: Accelerated Corneal Collagen Cross-Linking, including Epi-off and Epi-on, shows a good efficacy and stabilization in keratoconus patients with non-statistically significant differences between the two groups at follow-up points 1, 3, 6, and 12 months after the procedure.